Os ourives em Santa Maria, RS: a história do ofício e da produção local de joias - Machado, Anderson (2022)
As a human creation, jewelry carries aesthetic and commercial values with subjective meanings related to memories and art. Throughout the ages, these artifacts have been configured as a link between the past and the present, between the real and the symbolic, becoming a material testimony of cultures of peoples. In the vast universe of jewelry, social and work relations stand out in addition to symbolic and mystical perspectives. Thus, this research presents a multidisciplinary study on the history of jewelry and the goldsmiths’ craft. Using a methodology that privileged the use of bibliographic sources, empirical data, and interviews, this study presents an overview of the evolution of jewelry in the world historical trajectory. Moreover, it highlights the Brazilian jewelry narrating important events that accompanied the development of the jewelry sector in the country. With the help of existing documents in places that safeguard collections on local memory, this research presents the history of jewelry in Santa Maria, RS, which possibly started with the arrival of German immigrants in the second half of the 18th century. To complement the history of local jewelry, interviews were also conducted to record and understand memories and other reports of goldsmiths and jewelers who work in the city. In addition to it, it was possible to know the reality of the local jewelry market and define its characteristics through a survey conducted with data obtained from the City Hall of Santa Maria. At the end of the study, the process of creating the product derived from the research is presented. This product is a book project entitled “The goldsmiths in Santa Maria, RS”, which is about local jewelry and is meant to be used as a historical and pedagogical subsidy for promoting educational actions, tourist dissemination of the city, and appreciation of this craft in Santa Maria.